Smartphone education improves embarrassment, bowel preparation, and satisfaction with care in patients receiving colonoscopy: A randomized controlled trail. Issue 46 (13th November 2020) - Wen, Ming-Chu; Kau, Kevin; Huang, Sheng-Shiung; Huang, Wen-Hsin; Tsai, Li-Yun; Tsai, Tsung-Yu; Tsay, Shiow-Luan
Abstract: Background: Colonoscopy is considered a safe and effective tool for detecting colorectal cancer. Nevertheless, the proportion of patients are hesitating to receive colonoscopy. Smartphone education may decrease the barrier of colonoscopy. The aim of this study is to examine the effectiveness of smartphone education in colonoscopy. Methods: We conducted a prospective, double-blinded, randomized, controlled study to examine the effectiveness of smartphone education on embarrassment, bowel preparation, and satisfaction in colonoscopy. The patients' embarrassment was measured by the colonoscopy embarrassment scale. The quality of the bowel preparation was evaluated by gastroenterologists according to the Aronchik Scale. The satisfaction of colonoscopy care was assessed by a satisfaction scale developed by the authors. Results: A total of 150 patients were analyzed in the smartphone education and control groups (n = 75 in each group). The smartphone education group reported fewer embarrassment ( B  = −2.78, P  = .02) than those of the control group, the patients who were older ( B  = .15, P  = .001) and who were male ( B  = 2.91, P  = .003) showed higher embarrassment. Additionally, smartphone education group were likely to have better colon preparation (odds ratio = 2.46, 95% confidence interval: 1.20–5.02) than that of the control group. Smartphone education also improved the satisfaction with care ( β  = 4.60, P  < .001), and above normal body mass index decreased the satisfaction with care ( β  = −0.19, P  < .05). Conclusion: Smartphone education improves embarrassment, bowel preparation, and satisfaction with care in patients receiving colonoscopy.